Membangun Politik Hukum Asas Legalitas dalam Sistem Hukum Pidana Indonesia - Author: Faisal (Fakultas Hukum Universitas Islam Indonesia, 2014)
This research is to discuss: first, what accounts for the reconceptualization of legality; and second, how to establish the legality principle law politics based on the social conditions of Indonesian society. This research is a normative legal study using the primary and secondary legal sources. This study concludes that first there is an adoption of characteristics which are against the formal law in legality principles of Criminal Code, namely the provision stating that a crime does exist in case of the fulfilment of the elements stated in the descriptiom of the case or accompanied by the consequences, which show that there is no place for unwritten law (customs) by looking at the existence of the characteristics of formal law violation. Second, ideas, concepts, values, of balance are the significant support in the legal political attempt of the legality principle using the prismatic concept (equilibrium value). The legality prismatic concept of the legality principle is originated from and oriented to the equilibrium of five pillars of Pancasila, which can be compacted into “three pillar equilibrium”, those are religion pillar, humanity pillar, and social pillar (nationalism, democracy, and social justice).